MENGAJARKAN KOSA KATA BAHASA INGGRIS: SUATU TINJAUAN PRAKTIS - Ignatia Maria Hendarti (Master Program in Linguistics, Diponegoro University, 2010)
This paper deals with a practical guide to teaching English vocabulary as an effective means for students to improve their literacy rate. A research report shows that a child (of English native speaker) can improve his/her vocabulary amazingly in a relatively short period of time. Therefore, based on this acquiring process, the writer of this paper suggests that learning vocabulary will be of paramount importance in teaching a foreign language, especially English. Some important approach and techniques mentioned in this paper can be used to help students improve their word power so that they can learn independently without any supervision of teachers